(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Different definitions of the Scythian—Anisian boundary are discussed. Based on taxa and sequence of Keyserlingites faunas at 19 Boreal localities and 6 Tethyan localities, Keyserlingites faunas are considered to be Late Sparhian in the Boreal province and Early Anisian in the Tethyan province. Keyserislingites not appropriate for cosmopolitan zoning. The base of Lenotropites—Japonites zone of Central Qinghai, China appears to indicate base Middle Triassic: it has abundant earliest Anisian ammonite faunas of mixed Boreal—Tethyan character (ecotone) providing direct correlation between these provinces. Correlations of Anisian (Aegean), Spathian and the Anisian—Scythian boundary are made between different localities, particularly between the Tethyan and Boreal provinces and between basin and platform facies. Olenikites zone is coeval to Subcolumbites zone; Lenotropites caurus zone to Lenotropites—Japonites zone; Columbites zone to Tirolites cassianus zone;and Subcolumbites zone to Tirolites carniolicus zone. Scythian—Anisian mixed faunas and stratigraphic condensation are also discussed.